The Position of Roman Slaves Social Realities and Legal Differences - Schermaier, Martin (Dependency and Slavery Studies, 2023)
Slavery takes many forms. This was also true in Roman antiquity, even though modern scholarship on Roman slavery paints the picture of a very homogenous institution. This volume intends to correct that perception. In it, renowned legal historians analyse juristic writings to showcase the social differences among slaves reflected in these texts. In this way, the papers collected here convey an impression of the complexity of Roman slave law.